Violencias ejercidas en los cuerpos enajenados : encierro terapéutico y privación de derechos civiles. Chile central (1850-1870) - María José Correa Gómez (Centre de Recherches sur les Mondes Américains, 2009)
This study explores the relationship between medical science, violence and the sick body in the context of Chilean early alienism through two perspectives : medical isolation (materialized through the Casa de Orates de Santiago) and the deprivation of civil rights through interdiction. The problematization of the asylum as a space of symbolic and material violence allow to explore the scope of contemporary medical authority, while the study of interdiction give us a different entrance to the analysis of violence and the place of the mentally ill in Chilean society.